2019
DOI: 10.1515/iral-2018-2008
|View full text |Cite
|
Sign up to set email alerts
|

How to become a woman without turninginto a Barbie”: Change-of-state verbconstructions and their role in Spanish as a Foreign Language

Abstract: Pseudo-copulative change-of-state (PCOS) verbs are predicates that involve a change in the composition of an entity undergoing a particular event. Due to their complex linguistic nature, these verbs are not easy to be accounted for and consequently, they represent a real challenge to language teachers and learners. First, this paper critically examines the specialized L1 and L2 literature on PCOS verbs in Spanish. Then, it is shown that previous studies are unable to provide a unanimous theory, but rather offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Previous work has highlighted the difficulty of formulating rules to guide categorization of Spanish verbs of becoming. Verb selection based on rules that describe, for example, slow/fast change or passive/active change, is somewhat overlapping and not clear-cut (Bybee & Eddington, 2006;Eddington, 1999;Ibarretxe-Antuñano & Cheikh-Khamis, 2019), making acquisition a notable challenge for L2 speakers. Instead, previous usage-based work that examined actual usage in corpus data (Brown & Cortés-Torres, 2012;Bybee & Eddington, 2006) suggests that a prototype-based rule may be most effective at guiding learners in the formation of semantic adjective clusters.…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has highlighted the difficulty of formulating rules to guide categorization of Spanish verbs of becoming. Verb selection based on rules that describe, for example, slow/fast change or passive/active change, is somewhat overlapping and not clear-cut (Bybee & Eddington, 2006;Eddington, 1999;Ibarretxe-Antuñano & Cheikh-Khamis, 2019), making acquisition a notable challenge for L2 speakers. Instead, previous usage-based work that examined actual usage in corpus data (Brown & Cortés-Torres, 2012;Bybee & Eddington, 2006) suggests that a prototype-based rule may be most effective at guiding learners in the formation of semantic adjective clusters.…”
Section: Present Studymentioning
confidence: 99%
“… 12 It is also possible that participants under inductive learning conditions may have engaged in rule searching and hypothesis testing, even if no explicit rule was provided. In this case, it can be expected that learners would have come up with rules that may have misled their learning attempts (given difficulties even among experts to formulate rules for the Spanish verbs of becoming; see, e.g., Ibarretxe-Antuñano & Cheikh-Khamis (2019)). Earlier work has also shown that engaging in the search for a complex rule without being given the rule, may not be necessarily conducive to better language learning (Reber, 1976).…”
mentioning
confidence: 99%